Safety in Industrial Radiography: A Short Review - Abd Razak, Nurqayyimah; Othman, Siti Amira; A. Halim, Ahmad Mustaqim (Emerging Advances in Integrated Technology, 2023)
Nuclear industry have increasing demand from the world because its advantages towards us. It can generate larger scale of energy using little material. However there is certain awareness to us.In 2011 Fukushima Daiichi nuclear incident happen in Japan because of tsunami giving a major damage towards environment and people it is the worst incident since Chernobyl. It give a lot damage and the land unliable for decades. Then, power plants radioactive waste radiation to environment. There are few incident related to radioactive waste and it is real life threat. These materials can be harmful to environment for decades to come. Radiography is a non-destructive method used by most industry to discover the structural properties of material or to check for any defect in the material that can cause a failure in the process. The type of radiation used by the industry for radiography technique is ionizing radiation such as x-ray and gamma radiation, it is a strong radiation source. Working with such   a dangerous radiation need some decent skills and protection to avoid any radiation exposure to the worker that will result in some serious health condition. Not only it can affect the worker, if it is handled recklessly, it can degrade the quality of the final product and causing pollution to environment. Therefore, an extreme safeguarding and professionalism is required for the radiation worker. In this review, will looked for the safety guidelines to improve the safety to environment and human in nuclear industry and will be focusing on the common radiation protection and procedure that has been implemented in industrial radiography